ISO Certification does it Matter? A Case of Pharmaceutical and Beverages Sector in Pakistan (Global Journal of Management and Business Research, 2014)
In this paper, comparison is made to know the impact of International Organization for Standardization (ISO) certification on organization's profit after certification and before certification. Randomly pharmaceutical and beverages sectors selected from Karachi Stock Exchange listed companies in Pakistan. The annual data of profit from (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) collected from Balance Sheet analysis (BSA) published by state bank of Pakistan (SBP).Mann Witney U test applied to compare two time periods and observed that there is significance difference between the profits of two time periods of both sectors.